"Ratio of fracture site diameter to isthmus femoral canal diameter" as a predictor of complication following treatment of infra-isthmal femoral shaft fracture with antegrade intramedullary nailing. Issue 4 (April 2021) - Yang, Tzu-Cheng; Tzeng, Yun-Hsuan; Wang, Chien-Shun; Lin, Chun-Cheng; Chang, Ming-Chau; Chiang, Chao-Ching
Highlight: Adequate length of the nail spanning the fracture site is important and distal screw should be located more than 3 cm from fracture site. The FI ratio could be a reliable predictor of complication after antegrade IM nailing. FI ratio equal or greater than 2 is strongly predictive for the occurrence of post-operative complication. Abstract: Introduction: Fixation of infra-isthmus femoral shaft fracture using antegrade intramedullary (IM) nailing is difficult and is associated with a high complication rate. This study aimed to identify risk factors for complications following this procedure. The ratio of the fracture site diameter to the diameter of the femoral intramedullary canal of the isthmus (FI ratio) was evaluated as a novel parameter to predict complication. Materials and methods: Patients who underwent antegrade IM nailing for infra-isthmus femoral shaft fracture between January 2008 and December 2018 and had a minimum of 12 months of follow-up were retrospectively reviewed. The primary outcome was occurrence of complication, including non-union, mal-alignment, fixation failure, or progressive loss of reduction. Logistic regression analysis was performed to identify risk factors of complication. The sensitivity and specificity of FI ratio as a predictor of complication was calculated. A receiver operating characteristic (ROC) curve was generated to establish an FI ratio threshold to predict occurrence of complication following antegrade IM nailing. Results: Sixty-five patients with a mean age of 47.1 years were included. Using univariate logistic regression analysis, comminuted fracture pattern ( p =0.026), distance from screws to fracture site (< 3cm) ( p =0.002), and higher FI ratio (p=0.001) were associated with complication. Using multivariate logistic regression analysis, FI ratio was identified as an independent risk factor for complication following antegrade IM nailing ( p =0.038). ROC curve indicated that FI ratio ≥ 2 had sensitivity and specificity of 0.72 and 0.72, respectively, in predicting complication. Conclusions: Our study indicates that wider intramedullary diameter at the fracture site was associated with higher complication rate following antegrade IM nailing in distal infra-isthmal femoral fractures. The FI ratio could be a reliable predictor of complication after antegrade IM nailing for such fracture, and alternative strategies should be considered for patients with higher FI ratio (≥ 2).